Effect of maternal anaemia on foetal Doppler indices during third trimester of pregnancy - Agrawal, Alka; Atram, Saurabh; Chaudhary, Vinod (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Anaemia is amongst the most common medical disorders encountered during pregnancy all over the world. India has a high rate of anaemia in pregnant women. Anaemia has a recognizable effect on both maternal and foetal health during pregnancy and on perinatal outcome, contributing remarkably to maternal morbidity and mortality. Routine foetal monitoring is an essential investigation for such females with special emphasis on obstetrics Doppler ultrasonography. Various changes due to foetal hypoxia due to maternal anaemia can be remarkably appreciated on Doppler helping in timely management. The objective of this study was to evaluate the effect of maternal anaemia on foetal Doppler indices. Methods: 400 pregnant women were assessed in a cross-section observational study done in the department of Radiodiagnosis in MYH, Indore, India. These women were divided into three groups of mild, moderate and severe anaemia based on the level of haemoglobin. Results: Umbilical artery resistive and pulsatility indices were found to be increased with the increasing severity of anaemia while middle cerebral artery indices and CPR showed a decreasing trend with the increasing severity of anaemia. Conclusions: We found that severe maternal anaemia is associated with marked adaption in foetal haemodynamics. Obstetrics Doppler can be used as an accurate measure of surveillance for foetal monitoring and will help in appropriate management.